Melatonin: Clinical Perspectives in Neurodegeneration - Cardinali, Daniel P. (Frontiers in Endocrinology, 2019)
Neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease (PD) are important health problems and there is a growing recognition that both governmental and non-governmental organizations must make efforts to prevent, in addition to treat, them. In this context, the pineal product melatonin has a promising significance. Melatonin, an unusual phylogenetically conserved molecule present in all known aerobic organisms, is effective both as a chronobiotic and as a cytoprotective. As a chronobiotic, the afternoon increase in melatonin "opens the doors of sleep" every night and the therapeutic use of melatonin has been demonstrated to preserve slow wave sleep effectively. As a cytoprotective molecule, melatonin reverses the low degree inflammatory damage seen in neurodegenerative disorders and ageing. One of the characteristics of advancing age is the gradual decrease in the circulating levels of melatonin. Both in vitro and in vivo, melatonin prevented the neurodegeneration observed in experimental models of AD and PD. Melatonin also increased removal of toxic proteins by the brain glymphatic system. A limited number of clinical trials have indicated that melatonin has a potential therapeutic value as a neuroprotective drug in the treatment of AD, particularly at an early stage of cognitive impairment, and of PD. From animal studies the cytoprotective effects of melatonin need high doses to become apparent (i.e. in the 40-100 mg/day range). The off-label use of melatonin is discussed.